Children Development As Consumers In Pakistan : Market Study To Set Up One Stop Hyper Retail Facility For Children In Pakistan - Mahmood Tahir, Atif (2004)
This report responds to the marketing research and analysis for the establishment of one stop retail facility for children in Pakistan. The concept behind this project paper is to introduce a retail facility in Lahore which would be selling all the major children's product lines under one roof.